2005
DOI: 10.1088/0953-4075/38/10/l07
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative recombination of rare gas hydride ions: II. ArH+

Abstract: A storage ring measurement of the rate coefficient for the production of neutral Ar in e + ArH+ collisions is described. It is found that the recombination rate is too small to measure at low centre-of-mass energies but the combined rate coefficient for dissociative recombination and dissociative excitation increases above 2.5 eV displaying peaks centred at 7.5 eV, 16 and 26 eV. Calculated potential energy curves for the ground and excited states of ArH+ are presented and these aid in the elucidation of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…The rate coefficient used for the ArH + + e − reaction, 10 −9 cm 3 s −1 , is an upper limit found experimentally by Mitchell et al (2005) Figure 13. Line surface brightness ratios relative to OH + 971 GHz versus the cosmic ray ionisation rate ζ in units of ζ 0 , for models with n H = 1900 cm −3 and a rate coefficient for ArH + + e − of 10 −11 cm 3 s −1 .…”
Section: Line While This Ohmentioning
confidence: 66%
See 1 more Smart Citation
“…The rate coefficient used for the ArH + + e − reaction, 10 −9 cm 3 s −1 , is an upper limit found experimentally by Mitchell et al (2005) Figure 13. Line surface brightness ratios relative to OH + 971 GHz versus the cosmic ray ionisation rate ζ in units of ζ 0 , for models with n H = 1900 cm −3 and a rate coefficient for ArH + + e − of 10 −11 cm 3 s −1 .…”
Section: Line While This Ohmentioning
confidence: 66%
“…The grid was rerun with reduced electron recombination rates of 10 −10 and 10 −11 cm 3 s −1 in order to investigate the effects on the abundance of ArH + . The highest gas temperature reached in any of the PDR models is around 12000 K, corresponding to a thermal energy of about 1.0 eV, while Mitchell et al (2005) found the reaction rate for electron energies below 2.5 eV was negligible. Figure 13 shows the relative line surface brightnesses versus ζ for a cloud density of 1900 cm −3 , this time with the ArH + + e − reaction rate set to 10 −11 cm 3 s −1 .…”
Section: Line While This Ohmentioning
confidence: 90%
“…The latter number is the sum of the branching ratios of channels (RC8b) and (RC8c), to which we have assigned equal values. For DR of ArH + (RC9), there are apparently no data, with the exception of an upper limit of 1 Â 10 À9 cm 3 s À1 , which was measured by Mitchell et al (2005). We adopt this value as the thermal DR coefficient with the temperature dependence of T À0:5 e .…”
Section: Rate Coefficients For Specific Dissociative Recombination Rementioning
confidence: 99%
“…(8) Mitchell et al (2005b). (9) Unshielded rate based on theoretical cross-sections of Alexseyev et al (2007).…”
Section: Basic Features Of Argon Chemistrymentioning
confidence: 99%